Study of gallstones in a population of patients under 25 years of age: Regarding 30 cases - Colet, Andrés; Domínguez, Juan; Olivera, Dercilio; Juri, Héctor; Estefan, Alberto (Cirugía del Uruguay, 1986)
Retrospective study of 30 patients under 25 years old with choletithiasis. The clinical signs were acule obstructive cholecystopathy in (FA 0,80), acule simple cholangitis (FA 0,08) and chronic cholecystopathy (FA 0,09). No post-operative mortality. Morbilily: parietal suppuration, 2 cases. Subphrenic abscesses, 1 case. And choledocho residual lithiasis, 4 cases. Early diagnosis and treatment is recommended for better results